“It’s Not Always Possible to Live Your Life Openly or Honestly in the Same Way” – Workplace Inclusion of Lesbian and Gay Humanitarian Aid Workers in Doctors Without Borders - Rengers, Julian M.; Heyse, Liesbet; Otten, Sabine; Wittek, Rafael P. M. (Frontiers in Psychology, 2019)
In this exploratory study, we present findings from semi-structured interviews with 11 self-identified lesbian and gay (LG) humanitarian aid workers of Doctors without Borders (MSF). We investigate their perceptions of workplace inclusion in terms of perceived satisfaction of their needs for authenticity and belonging within two organizational settings, namely office and field. Through our combined deductive and inductive approach, based on grounded theory, we find that perceptions of their colleagues’ and supervisors’ attitudes and behaviors, as well as organizational inclusiveness practices play a role in LGs’ perceived authenticity, but not belonging, in the workplace. However, these organization-level characteristics do not account for between-participant differences in perceived authenticity. Therefore, we inductively construct a typology of three groups, which we coined conscious first-missioners, authentic realists, and idealistic activists, based on how LG humanitarian aid workers assess and deal with not being able to be their authentic selves when they are in the field, because homosexuality is illegal in many project countries. Conscious first-missioners are separated from the other two groups based on having gone to the field once, whereby they felt in control over the decision on how to manage their sexuality. Alternatively, authentic realists and idealistic activists alike felt they did not really have a choice in how to manage their sexuality, but handled that differently. We find the importance of one’s sexuality as well as adherence to the overarching organizational mission relevant individual-level factors herein. Furthermore, we find disclosure of sexual identity to be strongly context-dependent, as participants are ‘out of the closet’ in the office, but go back into the closet when they enter the field, with different country contexts even leading to different decisions concerning self-disclosure, thus demonstrating the importance of careful sexual identity management. This so-called disclosure dilemma, we find, may not be merely an individual choice, but rather a shared dilemma involving multiple stakeholders, such as the organization and fellow team members. We discuss the findings’ contributions to existing literature on LGs’ workplace experiences and implications for future research on inclusion of sexual and other invisible minorities in the workplace.